2009
DOI: 10.1073/pnas.0901833106
|View full text |Cite
|
Sign up to set email alerts
|

Quantum control experiment reveals solvation-induced decoherence

Abstract: Coherent control holds the promise of becoming a powerful spectroscopic tool for the study of complex molecular systems. Achieving control requires coherence in the quantum system under study. In the condensed phase, coherence is typically lost rapidly because of fluctuating interactions between the solvated molecule and its surrounding environment. We investigate the degree of attainable control on a dye molecule when the fluctuations of its environment are systematically varied. A single successful learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…The phenomena were attributed to the influence of the environment. A subsequent study showed that such controllability is solvent dependent [211]. A theoretical demonstration that phaseonly control is possible in weak field for an open quantum system soon followed [212].…”
Section: State Of the Artmentioning
confidence: 99%
“…The phenomena were attributed to the influence of the environment. A subsequent study showed that such controllability is solvent dependent [211]. A theoretical demonstration that phaseonly control is possible in weak field for an open quantum system soon followed [212].…”
Section: State Of the Artmentioning
confidence: 99%
“…A subsequent study by van der Walle et al showed that such controllability is solvent dependent. 8 A careful examination of the assumptions can resolve the discrepancy between theory and experiment, considering that the experiments were carried out for an open quantum system. It has been suggested that the coupling to the environment changes the conditions under which the statement of impossibility holds.…”
Section: Introductionmentioning
confidence: 99%
“…OCEs have been successfully performed for a wide range of goals, including the control of molecular vibrational [13][14][15][16][17][18][19][20] and electronic states [21][22][23][24][25][26][27][28][29], the generation and coherent manipulation of X-rays [30][31][32][33][34], the control of decoherence processes [35,36], the selective cleavage and formation of chemical bonds [37][38][39][40][41][42][43], the manipulation of energy flow in macromolecular complexes [44][45][46][47], and the control of photoisomerization reactions [48][49][50][51][52]. Optimal control theory (OCT) [7,9,[53][54][55][56] has provided insights into the coherent control of a variety of quantum phenomena, such as electron transfer …”
Section: Introductionmentioning
confidence: 99%